Translating knowledge into practice: content analysis of online resources about sexual difficulties for individuals with traumatic brain injury - Moreno, Jhon Alexander; das Nair, Roshan (Taylor & Francis, 2015)
For many individuals with traumatic brain injury (TBI), the Internet is the only available source of information regarding their sexual problems following TBI. This study aimed to evaluate the content and the quality of patient or carer information that is readily available on the Internet about specific aspects of sexuality after TBI. A purposive (non-exhaustive) sample of eight leaflets available on the Internet related to sexuality following TBI was analysed using content analysis. Decreased desire was reported as the main sexual difficulty following TBI (87.5%), followed by inappropriate sexual behaviour (62.5%). Among the strategies to overcome these difficulties, all leaflets recommended seeking help from healthcare professionals; 42.8% were centred on the carer or the family, and only 28.5% was directly addressed to the individual with TBI. The information available overemphasises disinhibition, underscores other aspects of sexuality (e.g. sexual risk and inability to fantasise), and is conceived mainly for carers and families. A bias assuming that most individuals with TBI are involved in a romantic relationship was also present. Adolescents, women, older people, single people, and non-heterosexual individuals were not adequately represented. There is a need for Internet resources to provide specific recommendations for these groups.